2021
DOI: 10.1021/acsnano.1c03072
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Nucleic Acids for Near-Infrared Light-Responsive Self-Delivery of Small-Interfering RNA and Antisense Oligonucleotide

Abstract: Herein, we developed a photolabile spherical nucleic acid (PSNA) for carrier-free and near-infrared (NIR) photocontrolled self-delivery of small-interfering RNA (siRNA) and antisense oligonucleotide (ASO). PSNA comprised a hydrophilic siRNA shell with a hydrophobic core containing a peptide nucleic acid-based ASO (pASO) and NIR photosensitizer (PS). The incorporation of a singlet oxygen (1O2)-cleavable linker between the siRNA and pASO allowed on-demand disassembly of PSNA in tumor cells once 1O2 was produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 42 publications
0
65
0
Order By: Relevance
“…2b and c and S5†) that PHAA based nanoparticles achieve non-colocalization with lysosomes, there may be some related mechanisms, such as endosomal leaking, reverse vesicle fusion, inclusion body-Golgi vesicle transport and so on. 51–54 Overall, the above results demonstrated that PHA-based SNA nanoparticles showed effective ASO delivery and good improvement of cell uptake.…”
Section: Resultsmentioning
confidence: 62%
“…2b and c and S5†) that PHAA based nanoparticles achieve non-colocalization with lysosomes, there may be some related mechanisms, such as endosomal leaking, reverse vesicle fusion, inclusion body-Golgi vesicle transport and so on. 51–54 Overall, the above results demonstrated that PHA-based SNA nanoparticles showed effective ASO delivery and good improvement of cell uptake.…”
Section: Resultsmentioning
confidence: 62%
“…For example, Chen et al prepared a photolabile spherical nucleic acid for light-responsive codelivery of antisense oligonucleotide and siRNA. Upon exposure to an NIR laser, the prepared nanoplatforms rapidly oxidized and dissociated with continuous responsive release, resulting in a positive effect on tumor treatment [ 400 ]. Xu et al designed a light stimuli-responsive nanoparticle to achieve long blood circulation, enhanced tumor accumulation and penetration, and rapid body elimination in an imaging-guided treatment.…”
Section: Stimuli-responsive Targeting Strategiesmentioning
confidence: 99%
“…Recently, a photolabile spherical nucleic acid for carrier-free and near-infrared photo-controlled self-delivery of small interfering RNA (siRNA) and antisense oligonucleotides (ASOs) was also published. By incorporating a thioketal linker between the SiRNA and the peptide nucleic acid-based ASO, on-demand disassembly of photolabile spherical nucleic acid in tumors cells is possible once the 1 O 2 is produced by the inner PS upon NIR irradiation [ 198 ]. Furthermore, nanoparticle type vehicles also have been functionalized with a ROS cleavable linker in order to obtain light-triggered drug release (see Figure 13 ) [ 199 , 200 , 201 , 202 , 203 ].…”
Section: 1 O 2 In Bioorganic Chemistry Ap...mentioning
confidence: 99%